The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s10029-014-1262-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of sutured versus bovine pericardium mesh abdominal closure after open abdominal aortic aneurysm repair

Abstract: The bovine pericardium mesh reinforcement of fascia closure in patients undergoing open AAA repair showed effectiveness and low complication rate in prophylaxis from incisional herniation. It should be considered as an alternative mesh material in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(88 citation statements)
references
References 25 publications
0
83
0
5
Order By: Relevance
“…1 ). In total, 13 RCTs fulfilled the inclusion criteria, but the study of Timmermans and colleagues was excluded because only the short‐term results (postoperative complications in the first month) were discussed; thus 12 RCTs were analysed. Six studies were considered to have a low risk of bias, and six to have a high risk of bias ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). In total, 13 RCTs fulfilled the inclusion criteria, but the study of Timmermans and colleagues was excluded because only the short‐term results (postoperative complications in the first month) were discussed; thus 12 RCTs were analysed. Six studies were considered to have a low risk of bias, and six to have a high risk of bias ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Incisional hernia (IH) is a frequent complication after abdominal surgery, with an incidence ranging from 11 to 20 per cent in general surgical populations. The incidence of IH can increase up to 40 per cent in high‐risk groups, such as patients with an abdominal aortic aneurysm (AAA) or morbid obesity. IH may be asymptomatic, but can also lead to serious and potentially fatal complications, such as incarceration and strangulation of bowel.…”
Section: Introductionmentioning
confidence: 99%
“…Distribution of IDEAL stage and GRADE quality of included studies are presented in Tables and respectively. Of the four prophylaxis studies, two evaluated biological mesh at the time of stoma closure, one following midline laparotomy after abdominal aortic aneurysm (AAA) repair, and one after cytoreduction and hyperthermic intraperitoneal chemotherapy. All four studies included only elective patients and the degrees of contamination were clean‐contaminated (2) and contaminated (2).…”
Section: Resultsmentioning
confidence: 99%
“…Mesh placement was reported as intraperitoneal in five studies 34,35,42,44,46 , extraperitoneal in seven 30,32,33,37,40,48,50 and a combination in ten studies 29,31,36,38,39,41,43,45,47,49 . One study 28 26 2015 Greece Prophylaxis Bovine pericardium 36 Maggiori et al 24 2015 France Prophylaxis Strattice™ 17 Ueno et al 29 2004 USA Reinforcement Surgisis ® 16 Limpert et al 37 2009 USA Reinforcement Bovine pericardium 22 Hsu et al 35 2009 USA Reinforcement Permacol™ 16 Chavarriaga et al 32 2010 USA Reinforcement Permacol™ 7 Cox et al 48 2010 USA Reinforcement Surgisis ® 10 Shah et al 45 2011 elective and emergency operations. The eight studies involved a mixture of procedures, with degree of contamination ranging from clean-contaminated to dirty.…”
Section: Ideal Stage Of Innovation and Grade Quality Of Evidencementioning
confidence: 99%
“…It has been found that bovine pericardium can be a good alternative in the reconstruction of congenital diaphragmatic hernia in children [34]. At the same time, there are unique communications reflecting efficiency of use of bovine pericardium grafts in reconstruction of the abdominal wall [15,35], most of them being at the experimental stage [25,36].…”
Section: Color H-e;mentioning
confidence: 99%